Them and Us. Issue 2 (July 2016) - Jones, Lynne Myfanwy
Abstract : This personal reflection addresses the author's experience while working in the most northern and poorest province of Mozambique. It draws on an ethnographic assessment, conducted over three months in the area. Mothers were interviewed on how they raise their children and what are their main concerns. The stories illustrate the enormous difficulties they face in both meeting their basic needs and the hardships of life as a woman in this area. The reflection also explores the questions raised by a common model of practice in both humanitarian and development settings in which paid professional aid workers depend upon the use of poorly paid local staff and large numbers of unpaid local volunteers to carry out their interventions. The practical and ethical consequences of this model of intervention are discussed.